Factors Associated with Prolonged Opioid Use after CMC Arthroplasty - Zamri, Meryam; Lans, Jonathan; Jupiter, Jesse B.; Eberlin, Kyle R.; Garg, Rohit; Chen, Neal C. (Journal of Hand and Microsurgery, 2021)
Background Higher rates of prolonged opioid use have been reported in patients who undergo thumb carpometacarpal (CMC) arthroplasty compared with other hand procedures. Therefore, the aim of this study is to identify the risk factors associated with prolonged postoperative opioid use after CMC arthroplasty, along with reporting the number of patients who filled an opioid prescription more than 30 days postoperatively.Materials and Methods Retrospectively, 563 opioid-naïve patients who underwent CMC arthroplasty were included. A manual chart review was performed to collect patient characteristics, and opioid use was determined based on opioid prescription by a physician. Prolonged opioid use was defined as an opioid prescription at 90 to 180 days postoperatively. A multivariable analysis was performed to identify independent factors associated with an opioid prescription at 90 to 180 days postoperatively. Patients had a median age of 60.4 years (interquartile range [IQR]: 55.5–66.9) and had a median follow-up of 7.6 years (IQR: 4.3–12.0).Results The rates of postoperative opioid use ranged from 6.2% (53 out of 563 patients) at 30 to 59 days postoperatively to 3.9% (22 out of 563 patients) at 150 to 180 days postoperatively. In total, 17.1% (96 out of 563 patients) received a second opioid prescription more than 30 days following surgery, of which 10.8% (61 out of 563 patients) were between 90 and 180 days postoperatively. Older age, defined as a median of 63 years (IQR: 57.10–69.88) (p = 0.027, odds ratio [OR] = 1.04) and a history of psychiatric disease (p = 0.049, OR = 1.86) were independently associated with prolonged opioid use.Conclusion A prolonged opioid use rate of roughly 11% was found in opioid-naïve patients who underwent CMC arthroplasty. In patients at risk (older patients or psychiatric history) of prolonged opioid use, careful postoperative pain management is recommended.
Keywords: hand surgery; opioids; CMC arthroplasty; prolonged opioid use; opioid-naïve patients; opioid prescription